Arterial and venous thrombosis of the cerebral vasculature in GAPO syndrome. Issue 5 (24th March 2014) - Zeydan, Burcu; Benbir, Gulcin; Uluduz, Derya; Ince, Birsen; Goksan, Baki; Islak, Civan
<x xml:space="preserve">Abstract</x> A 37‐year‐old male, previously diagnosed with GAPO syndrome, was admitted to our hospital complaining of recurrent episodes of transient weakness and numbness in his left arm for 3 months, and severe headache with progressive dysphagia for 15 days. His cranial magnetic resonance (MR) images showed multiple ischemic foci in the bilateral periventricular and supraventricular white matter. Cerebral MR‐angiography showed total occlusion of the right internal carotid artery and moderate stenosis in the left internal carotid. We also detected chronic thrombotic changes in the distal left sigmoid sinus, proximal right sigmoid sinus, and bilateral jugular veins on cerebral MR‐venography. He was diagnosed with dilated cardiomyopathy at age 31 years, which was reported as a novel association; and later he had a myocardial infarction at age 34 years. To the best of our knowledge, this is the first patient with GAPO syndrome and arterial atherosclerosis in cerebral—as well as coronary—arteries and intracranial venous thrombosis. We report the evolution of the disease in this patient, who died at age 38 years due to respiratory failure secondary to lower respiratory tract infection. © 2014 Wiley Periodicals, Inc.